Engagement System in BBC The Big Questions: Appraisal Approach - La Ajina Hasibuan, Faninsky Aryanti; Deliana, Deliana; Nurlela, Nurlela; Setia, Eddy; Rangkuti, Rahmadsyah (Master Program in Linguistics, Diponegoro University, 2024)
In human communication, language is really important because it helps us express ourselves and connect with others by sharing ideas, feelings, and information. Appraisal Theory of Engagement explains how language and emotions are connected. Engagement with the audience involves creating a connection between the speaker or writer and the intended recipients of the message. The research employs qualitative techniques on kinds of engagement system reflected by the host of BBC: The Big Questions. The researcher will focus on BBC The Big Questions show from YouTube entitled “Is digital media good for democracy? BBC News.” The result showed that there are 7 Monoglossic clauses and 86 Heretoglossic clauses. The domination of Heterogloss clause on BBC The Big Questions show that the clauses said by the speakers are dominantly engaged with the viewpoints of other. The most heterogloss which found on the show is Entertain. There are 56 clauses out of 86 clauses. It shows that the percentage of Entertain is 65,1%. The domination of Entertain shows that the speakers explain their opinions as well as to open up possibilities in the viewpoints.